Significado do cuidado à pessoa com diabetes mellitus na perspectiva de enfermeiros da atenção básica de saúde - Paraizo, Camila Maria Silva (2018)
Given the magnitude of Diabetes Mellitus and its repercussions on different dimensions of life, it is essential that the multidisciplinary team, especially nurses, widen your eyes on these people. In the face of this panorama this study leads us to instigate questions about the knowing/doing/being of nurses in the care of the person with Diabetes Mellitus in the daily life of work, with the goal of understanding the meaning of care to the person with Diabetes Mellitus from the point of view of nurses basic health care. This is an ethnographic study anchored the Interpretative Anthropology, held between September 2016 to August 2017 with 16 nurses of basic health units and the family health strategy, interview techniques were used, participant observation and diary of field. The analysis of the data were constructed in three axes which cover the dimensions, managerial and educational outreach of the nursing care that proved full of complexities and features a plurality of meanings that guide the praxis of a trader. The semiotic look made possible understand how significant and the plurality of meanings are intertwined and are culturally constructed by social interactions, as these nurses visitors experience the challenges of care practice.